Examining the Impact of @waste4change's Instagram Campaign on User Attitudes towards Waste Management - Hereditha Alifia; Drina Intyaswati; Yuliani Widianingsih; Hermina Simanihuruk; Siti Maryam (Sultan Publisher, 2023)
Waste management is a social problem that needs to be addressed to foster a positive attitude toward the need to develop waste management. Campaigns through social media need to be evaluated for their benefits. Only a few studies have evaluated the impact of exposure and presentation of information conveyed via social media. This study aims to see the effect of exposure and presentation of information from @waste4change delivered through Instagram on user attitudes. The population is social media users, and a sample of 100 users is taken. The research used a survey with purposive sampling techniques, and the questionnaires were distributed through social media. The results show that exposure and information presentation significantly influence user attitudes. In addition, the presentation of information in this study showed the role of valence and weight of information. The findings confirm the role of Instagram platform content in providing education.